Soil elemental changes during human decomposition - Taylor, Lois S.; Gonzalez, Adrian; Essington, Michael E.; Lenaghan, Scott C.; Stewart, C. Neal; Mundorff, Amy Z.; Steadman, Dawnie W.; DeBruyn, Jennifer M. (PloS one, 2023)
Mammalian decomposition provides pulses of organic matter to the local ecosystem creating ephemeral hotspots of nutrient cycling. While changes to soil biogeochemistry in these hotspots have been described for C and N, patterns associated with deposition and cycling of other elements have not received the same attention. The goal of our study was to evaluate temporal changes to a broad suite of dissolved elements in soils impacted by human decomposition on the soil surface including: 1) abundant mineral elements in the human body (K, Na, S, P, Ca, and Mg), 2) trace elements in the human body (Fe, Mn, Se, Zn, Cu, Co, and B), and 3) Al which is transient in the human body but common in soils. We performed a four-month human decomposition trial at the University of Tennessee Anthropology Research Facility and quantified elemental concentrations dissolved in the soil solution, targeting the mobile and bioavailable fraction. We identified three groups of elements based on their temporal patterns. Group 1 elements appeared to be cadaver-derived (Na, K, P, S) and their persistence in soil varied based upon soluble organic forms (P), the dynamics of the soil exchange complex (Na, K), and gradual releases attributable to microbial degradation (S). Group 2 elements (Ca, Mg, Mn, Se, B) included three elements that have greater concentrations in soil than would be expected based on cadaver inputs alone, suggesting that these elements partially originate from the soil exchange (Ca, Mg), or are solubilized as a result of soil acidification (Mn). Group 3 elements (Fe, Cu, Zn, Co, Al) increased late in the decomposition process, suggesting a gradual solubilization from soil minerals under acidic pH conditions. This work presents a detailed longitudinal characterization of changes in dissolved soil elements during human decomposition furthering our understanding of elemental deposition and cycling in these environments.